2022
DOI: 10.1371/journal.pone.0279480
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D knowledge and sun exposure practices among Sri Lankan healthcare undergraduates

Abstract: Introduction Although overexposure to ultraviolet radiation may lead to skin cancer, inadequate exposure results in vitamin D deficiency (VDD). We explored vitamin D-related knowledge and sun exposure practices among Sri Lankan healthcare undergraduates. Methods The sampling frame consisted of medical and allied health undergraduates in a single centre. A newly developed, pre-piloted, self-administered questionnaire collected data on vitamin D knowledge, sun avoidance behaviour and outdoor time. Univariate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…For example, a study found that many university students in the United Arab Emirates did not receive sufficient sunlight, which could pose a public health problem due to a potential vitamin D deficiency ( 32 ). Additionally, a similar study found low sun exposure practices among Sri Lankan university students in healthcare studies ( 30 ), aligning with our findings. Moreover, other studies have highlighted how modern urban lifestyles, common among university students, limit sunlight exposure ( 31 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…For example, a study found that many university students in the United Arab Emirates did not receive sufficient sunlight, which could pose a public health problem due to a potential vitamin D deficiency ( 32 ). Additionally, a similar study found low sun exposure practices among Sri Lankan university students in healthcare studies ( 30 ), aligning with our findings. Moreover, other studies have highlighted how modern urban lifestyles, common among university students, limit sunlight exposure ( 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…This is exacerbated by technology and preference for indoor activities, which further reduces opportunities for exposure to natural sunlight ( 62 , 63 ). On the other hand, a lack of knowledge about vitamin D, long hours spent in academic facilities, and sedentary study habits are some of the reasons for low sunlight exposure ( 30 , 32 ); this is particularly relevant for Health Sciences and Engineering/Architecture students, whose rigorous academic programs often involve a greater amount of time spent indoors. The low sunlight exposure in these groups of university students suggests the need to encourage outdoor activities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations